Tunable amplified spontaneous emission in graphene quantum dots doped cholesteric liquid crystals. (23rd May 2017) - Cao, Mingxuan; Yang, Siwei; Zhang, Yating; Song, Xiaoxian; Che, Yongli; Zhang, Haiting; Yu, Yu; Ding, Guqiao; Zhang, Guizhong; Yao, Jianquan
Abstract: Graphene quantum dots (GQDs) have received much research attention, because of their useful structure and optical absorption/emission. We report the tunable amplified spontaneous emission (ASE) in GQD-doped cholesteric liquid crystal (CLC), which to the best of our knowledge has not been previously observed. The GQDs are uniformly dispersed with a weight ratio of 0.5 wt.% in CLC. Under optical excitation, typical ASE is triggered in the system at pump energies greater than 1.25 mJ cm −2 . The emission peak at the long wavelength edge of the photonic bandgap shifts from 662 to 669 nm, as the working temperature is increased from 50 to 90 °C. The preparation of the combined GQDs and CLC is simple and low-cost, and the resulting material is photostable and non-toxic. Combining the GQD gain material with the self-assembled CLC resonator has potential in the fabrication of ASE source and laser devices.